1999
DOI: 10.1007/bf02967179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of axillary lymph node status in breast cancer with MRI

Abstract: BACKGROUND: We performed a retrospective study to establish the optimal radiological criteria for axillary lymph node metastases from breast cancer by measuring all dissected nodes, and to determine whether magnetic resonance imaging (MRI) could reliably reveal axillary involvement. METHODS: Pathological findings and MRI scans of 202 patients with invasive breast cancer were reviewed. The long- and short-axis dimensions of all level I an II lymph nodes were measured microscopically, and then the long-to-short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 28 publications
2
61
0
1
Order By: Relevance
“…The sensitivity and specificity achieved using these techniques does not allow a reliable selection of patients for full axillary clearance or a more minimally invasive procedure. More recent advances such as dynamic contrast enhanced MRI has a sensitivity and an NPV of 100% (Yoshimura et al, 1999;Murray et al, 2002) and 2-[(18) F] fluoro-2-deoxy-Dglucose-PET has a sensitivity of 82 -95% and an NPV of 88% (Greco et al, 2001;Wahl, 2001). These two imaging modalities may be reliable in predicting the absence of nodal metastases in women with breast cancer, but these techniques are not readily available, are expensive and the results need to be confirmed in large multicentre studies.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity achieved using these techniques does not allow a reliable selection of patients for full axillary clearance or a more minimally invasive procedure. More recent advances such as dynamic contrast enhanced MRI has a sensitivity and an NPV of 100% (Yoshimura et al, 1999;Murray et al, 2002) and 2-[(18) F] fluoro-2-deoxy-Dglucose-PET has a sensitivity of 82 -95% and an NPV of 88% (Greco et al, 2001;Wahl, 2001). These two imaging modalities may be reliable in predicting the absence of nodal metastases in women with breast cancer, but these techniques are not readily available, are expensive and the results need to be confirmed in large multicentre studies.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has been reported to have a sensitivity of 79% [5] and this might be further improved by dynamic contrast-enhanced MRI [6]. Shimizu et al [11] found that visualization of axillary lymph node metastasis by IV-DSA correlated with higher MVD within the lesion than in nonmetastatic nodes, and suggested that IV-DSA assesses the neovascularization of lymph nodes that become metastasis-positive.…”
Section: Discussionmentioning
confidence: 97%
“…A number of diagnostic imaging modalities are currently available for the evaluation of axillary node metastasis, including ultrasonography [1,2], computed tomography (CT) [3,4], and magnetic resonance imaging (MRI) [5,6], and more recently positron emission tomography (PET) has been shown to provide useful information in these patients [7]. However, none of these modalities may yet be considered to be a definitive method.…”
Section: Introductionmentioning
confidence: 98%
“…A study by Gajdos et al [25] found that main tumor size and age were independently associated with lymph node metastases. Yoshimura et al [18] studied axillary lymph node status in breast cancer patients. Of 97 axilla lymph nodes, 27 showed eccentric cortical hypertrophy, and all were pathologically malignant.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies have predicted lymph node status by assessing the size and shape of lymph nodes [18][19][20][21]. Attempts at axillary staging by means of anatomical imaging of the axilla with CT or magnetic resonance imaging (MRI) have proved more useful than clinical examination [22].…”
Section: Introductionmentioning
confidence: 99%